Regulatory Role of Some Protein Kinases in Signal Transduction Pathways in Heart Health and Disease - Nusier, Mohamad; Elimban, Vijayan; Jaykishan Prasad, Jaykishan; Shah , Anureet K; Dhalla, Naranjan S (Scripta Medica, 2023)
Various protein kinases including protein kinase A (PKA), Ca2+-calmodulin kinase (CaMK), phosphoinositide 3-kinase (PI3K), protein kinase C (PKC) and mitogen-activated protein kinase (MAPK: ERK1/2, p38-MAPK and JNK) are integral part of different signal transduction pathways, which are known to regulate cardiac structure, function and metabolism. In addition, these signal transducing proteins are involved in the regulation of cation transport, cellular growth, gene expression, apoptosis and fibrosis by modifying the function of different target sites of subcellular organelles in the myocardium. However, the information regarding these signal transducing molecules is scattered and mechanisms of their involvement in diverse regulatory processes are poorly understood. While PKA, CaMK, PI3K and PKC are activated by different hormones and mechanical stimuli, MAPKs are activated by growth factors and some cellular stresses such as oxidative stress, inflammation and Ca2+-overload. Each type of these protein kinases is expressed in the form of two or more isozymes showing different biochemical characteristics and distinct biological functions. It has been demonstrated that all specific isoforms of these kinases produce both beneficial and detrimental effects on the heart, which are dependent upon the intensity and duration of stimulus for their activation. While PKA, PKC and CaMK are mainly involved in augmenting cardiac function as well as inducing cardiac hypertrophy and arrhythmias, PI3K is mainly involved in maintaining β-adrenoceptor function and inducing inflammation as well as arrhythmias. On the other hand, ERK1/2 mainly participate in the genesis of cardiac hypertrophy and cytoprotection whereas p38-MAPK and JNK are primarily involved in cardiac dysfunction, apoptosis and fibrosis. Since the activities of most protein kinases are increased under prolonged pathological conditions, a wide variety of their inhibitors have been shown to produce beneficial effects. However, extensive research needs to be carried out to understand the pathophysiology of different isoforms of each protein kinase as well as for the development of their isoform-specific inhibitors.